2018
DOI: 10.1128/jb.00727-17
|View full text |Cite
|
Sign up to set email alerts
|

Two rsaM Homologues Encode Central Regulatory Elements Modulating Quorum Sensing in Burkholderia thailandensis

Abstract: The bacterium possesses three-acyl-l-homoserine lactone (AHL) quorum sensing (QS) systems designated BtaI1/BtaR1 (QS-1), BtaI2/BtaR2 (QS-2), and BtaI3/BtaR3 (QS-3). These QS systems are associated with the biosynthesis of -octanoyl-homoserine lactone (C-HSL), -3-hydroxy-decanoyl-homoserine lactone (3OHC-HSL), and -3-hydroxy-octanoyl-homoserine lactone (3OHC-HSL), which are produced by the LuxI-type synthases BtaI1, BtaI2, and BtaI3 and modulated by the LuxR-type transcriptional regulators BtaR1, BtaR2, and Bta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…S5 ). Accordingly, we observed that C 8 -HSL, 3OHC 10 -HSL, and 3OHC 8 -HSL concentrations were all increased in an rsaM2 mutant compared to the wild-type strain ( 24 ), indicating that RsaM2 likely intervenes in the regulation of all QS systems of B. thailandensis E264.…”
Section: Discussionmentioning
confidence: 82%
“…S5 ). Accordingly, we observed that C 8 -HSL, 3OHC 10 -HSL, and 3OHC 8 -HSL concentrations were all increased in an rsaM2 mutant compared to the wild-type strain ( 24 ), indicating that RsaM2 likely intervenes in the regulation of all QS systems of B. thailandensis E264.…”
Section: Discussionmentioning
confidence: 82%
“…Chromosomal integration of the mini-CTX- scmR-lux transcriptional reporter at the attB locus in B. thailandensis E264 strains was performed through conjugation with the auxotrophic E. coli χ7213, as described previously (12). Successful chromosomal insertion of scmR - lux was confirmed by PCR using appropriate primers.…”
Section: Methodsmentioning
confidence: 99%
“…These QS systems are referred to as the BtaI1/BtaR1 (QS-1), BtaI2/BtaR2 (QS-2), and BtaI3/BtaR3 (QS-3) QS systems in B. thailandensis (10, 11). The QS-1 system is composed of the BtaR1 transcriptional regulator and the BtaI1 synthase, which synthesizes N- octanoyl-L-homoserine lactone (C 8 -HSL) (12, 13). The BtaR2 transcriptional regulator and the BtaI2 synthase that catalyze the biosynthesis of both N- 3-hydroxy-decanoyl-L-homoserine lactone (3OHC 10 -HSL) and N- 3-hydroxy-octanoyl-L-homoserine lactone (3OHC 8 -HSL) constitute the QS-2 system (12, 14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations